Media Sosial Sebagai Alternatif Strategi Dalam Pemasaran UMKM Jimbe Desa Ngoran - Anggana Fitri Atyanti; Muizu, Wa Ode Zusnita (Universitas Serang Raya, 2025)
Ngoran is known as a digital village that has economic potential. Jimbe is one of the potential MSMEs in Ngoran village. However, the success of marketing Jimbe MSME products via social media is still less than optimal. This is due to limited insight and capabilities of Human Resources (HR) in marketing via social media. Community Service (PPM) is important considering the rapid development of technology has an impact on MSME marketing strategies. Moreover, high business competition requires MSMEs to be agile towards change and digitalization. This article discusses the PPM program which aims to increase HR insight and capabilities in digital marketing, especially through social media. PPM is carried out through methods of situation analysis, discussion, counseling, mentoring and evaluation. This program provides intensive education and training on digital marketing strategies, use of social media platforms, as well as techniques for creating interesting and effective content. The results of the PPM that has been carried out are that activity participants gain a good understanding of digital marketing, especially through social media, as well as increasing participants' abilities in carrying out digital marketing.